Initial market assessment for resilient nature-based water solutions in Wadi Seer, Jordan - Dabbas, L.; Belhaj Fraj, Makram; Fragaszy, Stephen; Samarasekara, Vidhisha (International Water Management Institute, 2024)
This study is a part of the Al Murunah project funded by the Foreign, Commonwealth & Development Office (FCDO), UK, and implemented by the International Water Management Institute (IWMI) in collaboration with the International Union for Conservation of Nature (IUCN). Its overarching goal is to increase water security in Jordan in the face of climate change and land degradation, particularly targeting Wadi Seer by promoting Resilient Nature-Based Water Solutions (RNBWS). To this aim, study explores the market potential for scaling up and scaling out financial mechanisms for RNBWS, specifically focusing on empowering women and youth cooperative enterprises and contributing to spring restoration.